Dobra nowina - Stronnictwo Ludowe (1944-1949). (Gdynia : [s.n.], 1946)
Ulotka propagandowa nawołująca do głosowania 3xtak.
Keywords: Stronnictwo Ludowe (1944-1949) -- druki ulotne; Referendum -- Polska -- 1946 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne